Secure pay-per-view testbed - O'MAHONY, DONAL EDWARD (IEEE, 1995)
Trials of video on demand and pay-per-view systems are underway in many countries, and as a result, many cable and telecommunications companies are having to upgrade or replace their distribution networks. Video streams must be secure in order to prevent unauthorized viewing of the programs being transmitted, yet most existing security systems do not make use of the potential for bidirectional signalling in new and upgraded networks. It would prove more useful to many companies if they could use one system to test a number of different distribution networks to see if they save an acceptable quality of service. In this manner, a company could decide if existing networks could be used without substantial changes, or whether expensive upgrades or indeed replacements were justified
IEEE: International Conference on Multimedia Computing and Systems
PUBLISHED
Keywords: video on demand; pay per view